Optimizing Economic Potential through Recreational Sports Tourism Facilities at Langsa City Forest Park - Bangun, Brema; Rangkuti, Yoki Afriandy; Navera, Prista Cindi; Hamzah, M. Alif (Journal of Indonesian Tourism and Development Studies, 2025)
Protected forests located along the equator provide significant ecological services, such as oxygen production, water retention, and erosion control. The Langsa City protected forest, while ecologically valuable, has not fully leveraged its potential for tourism through recreational sports tourism infrastructure. This study aims to assess the readiness and safety of recreational sports tourism facilities in Langsa City's protected forest and explore their potential to contribute to local economic growth through tourism. A quantitative descriptive approach was employed, incorporating field-based inventory and percentage analysis. Data were collected through direct observation, interviews with local stakeholders, and documentation of the existing recreational sports tourism facilities. The key results showed that while most facilities were in good condition, there were critical issues: PT. PEKOLA had not implemented an effective marketing strategy to attract visitors from outside the region, there was a lack of trained personnel to manage the facilities, and the infrastructure was underutilized, limiting its economic impact on the surrounding community. This research highlights the untapped potential of protected forests to drive a tourism-based economy. To maximize these benefits, it is recommended that the marketing strategy be improved, local staff be trained, and facility utilization be enhanced.